PENERAPAN KARAKTER ANAK MELALUI GERAKAN 5 (S) - Bonavantura Angelina Naru; Maria Irene Duya; Maria Santriana Paba; Florentina Ceyn Moi; Gde Putu Arya Oka (STKIP Subang, 2025)
Early childhood education is a crucial foundation for character development; therefore, simple yet effective strategies such as the 5S Movement (Smile, Greet, Salute, Polite, and Courteous) are essential. This study aims to analyze the implementation of the 5S Movement as a strategy for shaping children’s character at TKK Tunas Bangsa Watumanu. The research employed a descriptive qualitative method with purposive sampling involving teachers, the principal, and students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, with data validity tested through triangulation. The results showed that the 5S principles were consistently applied in daily school routines, and children demonstrated improvements in politeness, empathy, and confidence. Teachers’ role modeling and supportive visual environments strengthened value internalization, while limited parental involvement remained a challenge. The effectiveness of the 5S Movement depends on teacher consistency, positive reinforcement, and strong school–home collaboration.